Islamist groups in the UK and recruitment - Mohammed Ilyas (Journal of Terrorism Research, 2013)
Since 2001 and 7/7 the search to find out why and how Muslims born in Europe join political and violence orientated Islamist groups has occupied policy makers and social scientist. The search has produced explanations that suggest social grievance, Islam and physiological problems are the motivations for why some Muslims join and act on behalf of Islamist groups in the UK. However, the approaches tend not to focus the role emotions generated from events that involve Muslim suffering play in some individuals becoming interested in acquiring and acting upon them. These events are often experienced variously by Muslims living in Europe through the media and are used by Islamist groups as resources to recruit. Consequently, this paper is based on interviews carried out with Islamists in the UK and tentatively discusses two process that take into account the emotional effect of events that concern Muslims in order to make sense of how some Muslims become compelled to acquire extreme ideas, act upon extreme ideas (independently or behalf of a group) or join Islamist groups.